2020
DOI: 10.1096/fj.201903040rr
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/Ca2+signaling pathway is essential for the regeneration of GABAergic neurons in planarianDugesia japonica

Abstract: The nervous system is one of the most complex and fascinating organ systems in the metazoan. Neural networks regulate many aspects of animal physiology and behavior. The longheld doctrine that neurons are only produced in the embryo 1,2 has been challenged by the discovery that neurogenesis persists in the central nervous system (CNS) of adult animals. 3 It is now accepted that adult neurogenesis is a widespread phenomenon in different metazoans. 4,5 As vertebrates, zebrafish have shown that adult neurogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 75 publications
4
12
0
Order By: Relevance
“…Many studies have shown that m-3M3FBS is a selective PLC activator in various systems, including snail neurons [39], neuronal cells [40], and mouse taste cells [41]. Our previous research found that down-regulation of DjPLCβ can lead to defects in regenerated brains resulting in partial brain deletion, and failure of posterior brain lateral branches to regenerate [32]. In this study, we demonstrate that the U73122 strongly inhibits brain regeneration in planarian (Figs.…”
Section: U73122 Generated Brain Defects and M-3m3fbs Rescued Brain Defects During Head Regenerationsupporting
confidence: 56%
See 4 more Smart Citations
“…Many studies have shown that m-3M3FBS is a selective PLC activator in various systems, including snail neurons [39], neuronal cells [40], and mouse taste cells [41]. Our previous research found that down-regulation of DjPLCβ can lead to defects in regenerated brains resulting in partial brain deletion, and failure of posterior brain lateral branches to regenerate [32]. In this study, we demonstrate that the U73122 strongly inhibits brain regeneration in planarian (Figs.…”
Section: U73122 Generated Brain Defects and M-3m3fbs Rescued Brain Defects During Head Regenerationsupporting
confidence: 56%
“…There are no studies on the relationship between PLC and GABAergic neuron regeneration in vertebrates. Our previous research found that down-regulation of DjPLCβ can affect the brain regeneration and decrease the number of GABAergic neurons in planarian [32]. Our results showed that DjGAD mRNA and protein were decreased in U73122-treated planarian compared with control animals (Figs.…”
Section: U73122 and M-3m3fbs Affect The Regeneration Of Gabaergic Neuronssupporting
confidence: 50%
See 3 more Smart Citations